Speakers' choice of frame in binary choice - Marc van Buiten; Gideon Keren (Judgment and Decision Making, 2009)
A distinction is proposed between extitrecommending for preferred choice options and extitrecommending against non-preferred choice options. In binary choice, both recommendation modes are logically, though not psychologically, equivalent. We report empirical evidence showing that speakers recommending for preferred options predominantly select positive frames, which are less common when speakers recommend against non-preferred options. In addition, option attractiveness is shown to affect speakers' choice of frame, and adoption of recommendation mode. The results are interpreted in terms of three compatibility effects, (i) extit{recommendation mode---valence framing compatibility}: speakers' preference for positive framing is enhanced under extitrecommending for and diminished under extitrecommending against instructions, (ii) extit{option attractiveness---valence framing compatibility}: speakers' preference for positive framing is more pronounced for attractive than for unattractive options, and (iii) extit{recommendation mode---option attractiveness compatibility}: speakers are more likely to adopt a extitrecommending for approach for attractive than for unattractive binary choice pairs.